2017
DOI: 10.1128/mcb.00183-17
|View full text |Cite
|
Sign up to set email alerts
|

The Ets2 Repressor Factor (Erf) Is Required for Effective Primitive and Definitive Hematopoiesis

Abstract: is a gene for a ubiquitously expressed Ets DNA-binding domain-containing transcriptional repressor. haploinsufficiency causes craniosynostosis in humans and mice, while its absence in mice leads to failed chorioallantoic fusion and death at embryonic day 10.5 (E10.5). In this study, we show that is required in all three waves of embryonic hematopoiesis. Mice lacking in the embryo proper exhibited severe anemia and died around embryonic day 14.5. epiblast-specific knockout embryos had reduced numbers of circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
2
14
0
1
Order By: Relevance
“…ERF has recently been shown to be required for effective primitive and definitive hematopoiesis in mice. 37 Moreover, we noted that most of the eight CpG sites within the ERF promoter were hypermethylated in all three individuals in the HbF H group from WGBS data (Figure S2D). We subsequently validated this result with a bisulfite cloning method (Figure 1B), suggesting a possible association of ERF promoter hypermethylation with an elevated HbF level.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…ERF has recently been shown to be required for effective primitive and definitive hematopoiesis in mice. 37 Moreover, we noted that most of the eight CpG sites within the ERF promoter were hypermethylated in all three individuals in the HbF H group from WGBS data (Figure S2D). We subsequently validated this result with a bisulfite cloning method (Figure 1B), suggesting a possible association of ERF promoter hypermethylation with an elevated HbF level.…”
Section: Resultsmentioning
confidence: 83%
“…These findings are consistent with previous reports of impaired repopulation ability and quantitative differences in the differentiation of hematopoietic stem cells in the Erf-deficient mice. 37 We further noted that the variation of indel frequencies in the engrafted cells from edited mice were modest, 92% to 96% in BM cells and 85% to 90% in PB cells (Figure 3C), and that the indel frequencies in edited cells were consistent with that of input cells (88%), suggesting a high editing efficiency (Figure S7). Most importantly, in BM cells, we observed significant induction of g-globin in edited cells (mean of 22.4% of total b-like globin in edited cells compared with mean of 6.9% in unedited cells; Figure 3D).…”
Section: Validation Of Erf As An Hbf Repressor Via Engraftment Assays In Immunodeficient Micementioning
confidence: 76%
“…32,33 Erf can induce erythroid differentiation, 34 whereas recently, it has been suggested that Erf is required for effective primitive and definitive hematopoiesis counteracting the function of other ETS family members. 35 In this study, we investigated the role of Erf in T lymphocytes maturation in the thymus and its effects in the peripheral T lymphocyte populations. To this end, we generated thymus-specific conditional knockout mice and evaluated how the elimination of Erf in the thymus affects the generation of conventional CD4SP and CD8SP and γδ thymocytes as well as the production of thymic and peripheral Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…ERF (ETS2 repressor factor) is a human ETS family transcription factor initially identified as a repressor of another ETS family factor, ETS2, as signified by its name . ERF is expressed ubiquitously in all cell types and found to play critical roles in hematopoiesis, , formation of placenta, , osteogenesis, and cranial development. , Mutations in ERF were shown to cause syndromic craniosynostosis, a severe skull deformity resulting in disruption of normal brain development. , …”
mentioning
confidence: 99%